Study of excipients influence on the noopept releasing from the nasal dosage form - B. S. Burlaka; I. F. Bielenichev; V. V. Hladyshev (Zaporozhye State Medical University, 2019)
The development of medicines for fast delivery is the actual direction of modern pharmacy. In this connection, the nasal route of drug administration is perspective and has some advantages. The greater permeability of nasal mucosa with large surface area affords a rapid onset of therapeutic effect. The nasal route circumvents hepatic first-pass elimination associated with oral delivery; it is easily accessible and suitable for a patient. For the development of the new dosage form with nootropic and neuroprotective characteristics, the noopept was chosen. This substance has low toxicity, does not have any side effects, is characterized by the anti-oxidant and anti-inflammatory activity, decreases the calcium and glutamate neurotoxicity, improves rheological properties of blood. The aim of work is the determination of excipients' influence on the noopept releasing from the nasal dosage form. Materials and methods. For the investigation, the basic groups of excipients for the development of nasal dosage form were chosen: mucoadhesives and viscosity modifiers (polymers) and humectants (alcohols). Noopept releasing was studied using equilibrium dialysis by Kruvchinsky at 37 ± 0.5 °С through the semipermeable membrane - cellophane film "Kuprofan". Noopept concentration after 30 minutes was determined by the U -spectrophotometry at 258 nm. Results. According to the results of the carried out variance analysis, it was determined that for both factors Fexperim. > Ftabl., so the polymers and alcohols have a significant influence on the noopept releasing from the nasal dosage forms. After verification of average results of significant factors by the Dunkan's multiple rank test the next preferred series was built: sodium carboxymethylcellulose (chitosan) > sodium alginate (sodium hyaluronate); glycerol > sorbit > D-panthenol (without alcohol). Conclusions. It was determined that sort of polymer of hydrophilic bases and alcohols for moistening mucous membrane has a significant influence on noopept releasing from the nasal dosage forms. Sodium carboxymethylcellulose and chitosan with addition of glycerol provide with the optimal noopept releasing.